2015
DOI: 10.1038/eye.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of blindness and other degrees of sight impairment in patients treated for neovascular age-related macular degeneration in a well-defined region of the United Kingdom

Abstract: Aims This study aimed to evaluate the incidence and prevalence of blindness, sight impairment, and other visual acuity (VA) states in patients receiving ranibizumab for neovascular age-related macular degeneration (nAMD) in Gloucestershire. Methods Serial VA and injection data for all treatment-naive patients receiving their first intravitreal injections of ranibizumab for nAMD in the Gloucestershire National Health Service Ophthalmology department between 2008 and 2010 were extracted from an electronic medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…16 In a large cohort study from the United Kingdom, just 6.9% of nAMD patients became legally blind following 2 years of anti-VEGF, compared to a predicted figure of 15.7% for untreated patients. 17 The expected HALY gains per procedure that we estimate can be scaled up by applying case volumes. For example, in New Zealand, there are more than 75,000 anti-VEGF injections annually.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a large cohort study from the United Kingdom, just 6.9% of nAMD patients became legally blind following 2 years of anti-VEGF, compared to a predicted figure of 15.7% for untreated patients. 17 The expected HALY gains per procedure that we estimate can be scaled up by applying case volumes. For example, in New Zealand, there are more than 75,000 anti-VEGF injections annually.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this to be unlikely because the data in this analysis are from geographically well-defined regions of the United Kingdom, where few patients are thought likely to have sought separate or previous care from alternative ophthalmology centers. 18 Overall, this study has identified an association between previous intravitreal therapy and risk of PCR or vitreous loss during cataract surgery. The likelihood of PCR is estimated to be 1.04 times higher per injection or 2.59 times higher for those with 10 or more previous intravitreal injections after adjusting for case age, advanced cataract, and surgeon grade.…”
Section: Study Strengths and Limitationsmentioning
confidence: 95%
“…Treatment with intravitreal injections of anti-VEGF therapy results in improvement or stabilization of vision in over 90% of NVAMD patients [6]. Even with the profound impact of anti-VEGF therapy, CNV remains the leading cause of blindness due to AMD; furthermore, 7% of eyes treated for NVAMD become legally blind after 2 years [7,8]. …”
Section: Introductionmentioning
confidence: 99%